2008
DOI: 10.1152/ajpgi.00354.2007
|View full text |Cite
|
Sign up to set email alerts
|

Function, expression, and characterization of the serotonin transporter in the native human intestine

Abstract: Gill RK, Pant N, Saksena S, Singla A, Nazir TM, Vohwinkel L, Turner JR, Goldstein J, Alrefai WA, Dudeja PK. Function, expression, and characterization of the serotonin transporter in the native human intestine. Am J Physiol Gastrointest Liver Physiol 294: G254-G262, 2008. First published November 8, 2007 doi:10.1152/ajpgi.00354.2007.-The enteric serotonin transporter (SERT) plays a critical role in modulating serotonin availability and thus has been implicated in the pathogenesis of various intestinal disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
85
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 29 publications
12
85
0
Order By: Relevance
“…An original report by Wade et al (44) showed that most SERT was located in the crypts. In contrast, more recent studies in mouse, guinea pig, and human have shown SERT immunoreactivity in many epithelial cells throughout the crypt-villus axis (13,23,28,29) though not in the 5-HT-containing EC cells. How then do the actions of SERT affect the 5-HT signal?…”
Section: Discussionmentioning
confidence: 70%
“…An original report by Wade et al (44) showed that most SERT was located in the crypts. In contrast, more recent studies in mouse, guinea pig, and human have shown SERT immunoreactivity in many epithelial cells throughout the crypt-villus axis (13,23,28,29) though not in the 5-HT-containing EC cells. How then do the actions of SERT affect the 5-HT signal?…”
Section: Discussionmentioning
confidence: 70%
“…Hence, other proteins known to transport cations were considered, and SERT was chosen for further investigation for reasons outlined subsequently. SERT is expressed in both AP and BL membranes, although expression on the AP side is predominant in the intestine and Caco-2 cell monolayers (Wade et al, 1996;Martel et al, 2003;Gill et al, 2008), and it functions as an uptake transporter (Nelson and Rudnick, 1979). The endogenous substrate of SERT is serotonin; however, SERT and other OCTs share substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that PKA-dependent posttranslational modification of transcription factors Sp1 and Sp3 and their reduced DNA-binding activity may be responsible for the repression of NHE3 transcriptional activity by TNF-␣ and IFN-␥ (4). Furthermore, our recent studies showed that PKC␣ activation by serotonin leads to repression of both transcriptional and functional activity of NHE3 in intestinal epithelial cells (3,15). The role of PKC␦ and ERK1/2 as positive Fig.…”
Section: Discussionmentioning
confidence: 92%